Samurai with Telephones: Anachronism in Japanese Literature by Christopher Smith. Ann Arbor: University of Michigan Press, 2024. 242 pages - Citko-Duplantis, Małgorzata K. (Silva Iaponicarum, 2026)
Book review: Samurai with Telephones: Anachronism in Japanese Literature by Christopher Smith. Ann Arbor: University of Michigan Press, 2024. 242 pages.